Collaboration of a STEM-Based Blended Learning Model to Enhance Mathematical Comprehension - Esti Mungizzah; Sriyanto Sriyanto (Research and Innovation in Social Science Education Journal (RISSEJ), 2023)
Paradigms in the era of digitalization, particularly in the field of education in the use of Blended Learning in collaboration with the STEM approach (Science, Technology, Engineering, and Mathematics) as a guide for teachers in technological development capable of raising the standard of education in Indonesia. In class 5 SD N 3 Bangsa, a quantitative sampling model with probability is used as the research methodology. using observational and questionnaire data gathering methods, up to 32 students served as respondents. According to the statistical analysis, there is a substantial correlation between STEM-based Blended Learning and primary school student grasp of mathematics, with a significance value of 0.668. Blended Learning with a STEM focus significantly enhances students' mathematical comprehension of cube nets. Students struggle with smartphone operation uncertainty. It is okay to apply this learning technique for teaching social sciences, math, and science.